الولاية الصوفية عند الحكيم الترمذي - علي, ميساء (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
were not the mysticism saint hood alien to islamic thougts for being meffersa concept of secretion that thougt but the presence in the sufi thougt was not familiar even able sufis employed to suit their purposesand objectives aimed at the acquisition of knowledge and the attainment of spiritual perfection and communication with god under the name of the crown right .this word wich is toxic and spiritually to thoe who contact the particular divine as the divine scince knowledge miracles are not limited to the prophets alon vllaolia also luck of this treasure this appeared to say when the deceased wise al toormozy( 320) year of migration where he was the first one who laid the foundations of the mysticism saint hood theory integrated in line with the principles of mysticism and founded and paved the way for the idea of the perfection of holly men like the perfection of the prophetes he allowed each have working sufi to be called a holly man so he created arevolution in the world of Islamic Sufism in the sam time divine standard by which can be a mystic crown without effort like the superiority of the creator was adopted in order to justify to say varying holly men and all of them feature . لم تكن الولاية الصوفية غريبة عن الفكر الإسلامي لكونها مفهوماً مفرزاً من مفرزات ذلك الفكر ,إلا أن وجوده في الفكر الصوفي لم يكن مألوفاً إلى أن استطاع المتصوفة توظيفه بما يلائم أغراضهم وغايتهم التي هدفت إلى تحصيل المعرفة وبلوغ الكمال الروحي والإتصال بالحق تحت مسمى (ولي الحق) .هذا اللفظ الذي يعتبر وساماً روحياً لمن وصل واتصل بالذات الإلهية, حيث أن العلوم الإلهية والمعارف والمعجزات لاتقتصر على الأنبياء وحدهم . فاللأولياء أيضاً حظٌ من ذلك الكنز.ومفهوم الخاتم أيضاً لم يعد منوطاً فقط بالأنبياء (خاتم الأنبياء محمد صلوات الله عليه) بل هو شرف ورتبة لمن تقدم جميع الأولياء علماً وخلقاً وقرباً من الحق. إذْ ظهر هذا المفهوم بشكلٍ واضح عند الحكيم الترمذي المتوفى (320 هـ)، حيث اعتُبِر أول من أرسى دعائم الولاية الصوفية كنظرية متكاملة منسجمة مع مبادئ التصوف وأسسه، ومُهدَّ لفكرة ختم الأولياء على غرار ختم الأنبياء، وأباح لكل متصوف صَدقَ جَهْدَهُ الحق بالولاية (أن يسمى ولياً)، وبذلك أحدث ثورة في عالم الفكر الصوفي الإسلامي، مع أنه في نفس الوقت اعتمد المعيار الإلهي الذي بمقتضاه يمكن للمتصوف أن يكون ولياً دون جهد يبذله فضل وهبة من الخالق وذلك ليسوغ القول بمراتب الأولياء وخاصية كلٍّ منهم وهذا ما سنراه لاحقاً.